2016
DOI: 10.1002/chem.201504356
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Oxazolidine‐2,4‐diones Bearing Sulfur‐Substituted Quaternary Carbon Atoms by Oxothiolation/Cyclization of Ynamides

Abstract: A novel method for metal-free oxothiolation of ynamides to construct oxazolidine-2,4-diones bearing sulfur-substituted quaternary carbon atoms has been developed. It represents a rare C-O bond cleavage of ynamides, as well as a facile and tandem approach for the formation of C-O, C-S, and C-Cl bonds. This redox-neutral protocol can be applied to the synthesis of multisubstituted oxazolidine-2,4-diones with good chemoselectivity and good yields of isolated products under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…In 2016, Zhu and co-workers reported a cascade oxothiolation/cyclization of ynamides for the synthesis of thiooxazolidine-2,4-diones 124 mediated by arylthio chlorides under metal-free conditions (Scheme 35). 49 Notably, C–O bond cleavage of ynamides occurred in this transformation, followed by a facile and tandem C–O, C–S, and C–Cl bond formation. Mechanism study indicated that the solvent DMSO was involved in the formation of a carbonyl group.…”
Section: Thiolation Of Alkynesmentioning
confidence: 93%
“…In 2016, Zhu and co-workers reported a cascade oxothiolation/cyclization of ynamides for the synthesis of thiooxazolidine-2,4-diones 124 mediated by arylthio chlorides under metal-free conditions (Scheme 35). 49 Notably, C–O bond cleavage of ynamides occurred in this transformation, followed by a facile and tandem C–O, C–S, and C–Cl bond formation. Mechanism study indicated that the solvent DMSO was involved in the formation of a carbonyl group.…”
Section: Thiolation Of Alkynesmentioning
confidence: 93%
“…They can be representatively divided into the radical oxidation transformation ( Scheme 1a ) 4 e ,9,10 and ionic oxidation transformation ( Scheme 1b ). 11 For the radical oxidative transformation, O 2 is usually as an oxidant and converted into peroxy radical species. 4 e ,9 b – d ,10 a Differing from the radical oxidative conversion, S N 2′ is the major path for the ionic transformation with N -oxides or sulfoxides as organic oxidants.…”
Section: Introductionmentioning
confidence: 99%
“…A series of isoxazole derivatives such as 4-fluoro, selenyl, and boryl isoxazoles have been successfully accessed using this protocol (Scheme , eq 2). However, the electrophilic sulfenylation of 2-alkyn-1-one O -methyloximes, which can enable the construction of 4-sulfenyl isoxazoles, seems feasible but has never been established. Principally, this is attributed to the sulfenylation/halogenation of alkynyl derivatives with traditional S -electrophile (e.g., sulfenyl chloride), which is competitive to electrophilic cyclization and cannot be avoided properly . As our continuous work in the preparation of sulfur-containing compounds, herein we would like to report the electrophilic sulfenylation of 2-alkyn-1-one O -methyloximes using N -sulfanylsuccinimides or disulfides as electrophiles, which could access the synthesis of 4-sulfenyl isoxazoles under mild reaction conditions.…”
Section: Introductionmentioning
confidence: 99%